Sewing Skill Training In Improving Independence Of Deaf Children - Ndibo, Yaman La; Arfin, Arfin; Usman, Usman; Gustia, Waode (Program Studi Pendidikan Luar Sekolah FKIP Universitas Jember, 2024)
The purpose of this study was to determine the effectiveness of sewing skills training in increasing the independence of deaf children at Amet Jaya Raha Special High School, Muna Regency. The method used in this research is descriptive research method with a qualitative approach. Informants in this study amounted to 8 people . Informants consisting of 5 main informants, one key informant, and 2 additional informants. The instruments used in this study were observation sheets (observations, interview guides and documentation. The data collection technique used interviews and observation of the data obtained in the field and then analyzed and explained descriptively qualitatively. Until finally it could be concluded that a program could be said to be effective , if the achievement of goals is right on target and on time as a measure of success. With the implementation of this sewing training the SLB has a target to be achieved, namely that students can live independently in the future. The attitude of independence of students related to sewing skills has experienced a new increase reached approximately 50%.This shows progress in forming the independence of deaf children to dedicate to their future.Sewing skills training has an influence on behavior change, in the form of increased knowledge, skills, expertise so that it influences the growth of an attitude of independence. In the process of learning and training is certainly very good. After attending the training there were significant changes and improvements in skills